CUSTOMER EXPERIENCE DALAM LAYANAN BUS : SEBUAH IMPERATIF STRATEGIS DALAM MEMPERTAHANKAN CUSTOMER LOYALTY - Umi Latifah; M.Rifqy Roosdhani (Jurnal Bina Bangsa Ekonomika, 2024)
Various human activities make transportation services as a support in every activity. One of them is the intercity and interprovincial (AKAP) bus transportation service which from year to year is increasing. Thus, business owners must be able to compete and create innovation. The purpose of the research is to understand the impact of service quality and customer experience on customer loyalty through customer satisfaction at PO Bejeu Jepara. The approach used was quantitative with 110 samples analyzed using the SEM method using the Smart-PLS device version 4.0.  The tests are outer model tests, inner model tests, mediation tests, and hypothesis tests. The validity test is valid because the loading factor has a value greater than 0.7 and an AVE value greater than 0.5. Reliability tests are considered reliable, because composite reliability &; Cronbach's alpha have values greater than 0.7. From the mediation test, it was revealed that service quality to customer loyalty mediated by customer satisfaction was called Partial Mediation. Likewise with customer experience to customer loyalty mediated by customer satisfaction. The conclusion is that the quality of service and customer experience have a positive and significant effect on customer satisfaction and loyalty. In addition, customer satisfaction has a positive and significant impact on customer loyalty.